The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.jid.2015.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Oral Supplementation with Cocoa Extract Reduces UVB-Induced Wrinkles in Hairless Mouse Skin

Abstract: Cacao beans contain various bioactive phytochemicals that could modify the pathogeneses of certain diseases. Here, we report that oral administration of cacao powder (CP) attenuates UVB-induced skin wrinkling by the regulation of genes involved in dermal matrix production and maintenance. Transcriptome analysis revealed that 788 genes are down- or upregulated in the CP supplemented group, compared with the UVB-irradiated mouse skin controls. Among the differentially expressed genes, cathepsin G and serpin B6c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 54 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…We obtained (R)-1 via the same procedure applied for the synthesis of (S)-4. We finally examined the stereochemical effects on the skin wrinkle-reducing activity of the DHPVs, which was previously reported by us [18]. The ROS in skin tissue is frequently increased by UV radiation, which consequently causes an increase in expression of MMP-1 and transcription activity of AP-1.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…We obtained (R)-1 via the same procedure applied for the synthesis of (S)-4. We finally examined the stereochemical effects on the skin wrinkle-reducing activity of the DHPVs, which was previously reported by us [18]. The ROS in skin tissue is frequently increased by UV radiation, which consequently causes an increase in expression of MMP-1 and transcription activity of AP-1.…”
Section: Resultsmentioning
confidence: 79%
“…However, investigation on its biological effects were relatively rare, except for a few reports [13][14][15][16]. Despite the lack of studies on DHPVs' role in the biological system, several papers recently reported that DHPV exhibits a protective effect against UV-induced skin inflammation [17] or photoaging [18]. Particularly, Lee and Kim et al [18] recently reported that oral administration of DHPV reduced UV-induced skin-wrinkling via the regulation of genes involved in dermal matrix maintenance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated exposure to UV irradiation leads to ROS accumulation, photo-aging, and photocarcinogenesis [22]. Numerous studies reported that topical application of antioxidants engenders photo-protective effects and reduces UVB-induced inflammatory responses or ROS accumulation in hairless mouse skin [19,22,23]. ROS contributes to the induction of cellular senescence, as evidenced by premature ROS accumulation on treatment with antioxidants or inhibitors of cellular oxidant scavengers.…”
Section: Introductionmentioning
confidence: 99%
“…The hairless mouse has been established as a suitable animal model of photoaging during the last few decades. [9][10][11] The present experiments were conducted to explore the histopathological response of the hairless mouse dorsal skin to UV-B exposure after dietary alteration through calorie restriction (Cr) and the administration of an obesity diet. Histological variables of the diet-altered, UV-B-exposed animals were compared with those of appropriate control groups with light microscopic morphometry and immunohistochemistry.…”
mentioning
confidence: 99%